2013
DOI: 10.1051/0004-6361/201321210
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between internal waves and shear-induced turbulence in stellar radiation zones: the critical layers

Abstract: Context. Internal gravity waves (IGW) are known as one of the candidates for explaining the angular velocity profile in the Sun and in solar-type main-sequence and evolved stars due to their role in the transport of angular momentum. Our contribution deals with critical layers, which are defined as the locations where the Doppler-shifted frequency of the wave approaches zero (i.e., they correspond to corotation resonances). Aims. The IGW propagate through stably stratified radiative regions, where they extract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 75 publications
4
58
0
Order By: Relevance
“…It is then clear that a very effective mechanism for angular momentum transport is at work. Internal gravity waves are capable of transferring considerable amounts of angular momentum (Rogers 2015;Alvan et al 2013), which provides a suitable explanation for 'anomalous' rotation rates in other types of stars, such as those reported by Kurtz et al (2014); Saio et al (2015), and Triana et al (2015). However, Fuller et al (2014) showed that this mechanism falls short of explaining the observed rotation rate ratios in stars on the red giant branch.…”
Section: Introductionmentioning
confidence: 99%
“…It is then clear that a very effective mechanism for angular momentum transport is at work. Internal gravity waves are capable of transferring considerable amounts of angular momentum (Rogers 2015;Alvan et al 2013), which provides a suitable explanation for 'anomalous' rotation rates in other types of stars, such as those reported by Kurtz et al (2014); Saio et al (2015), and Triana et al (2015). However, Fuller et al (2014) showed that this mechanism falls short of explaining the observed rotation rate ratios in stars on the red giant branch.…”
Section: Introductionmentioning
confidence: 99%
“…With the large-scale meridional circulation (Zahn 1992;Mathis & Zahn 2004), the different hydrodynamical shear and baroclinic instabilities (Zahn 1983), and the fossil magnetic field (Gough & McIntyre 1998;Brun & Zahn 2006;Garaud & Garaud 2008;Duez & Mathis 2010;Strugarek et al 2011b), IGWs constitute the fourth main process responsible for the angular momentum redistribution in radiative interiors. Indeed, when they propagate, IGWs are able to transport and deposit a net amount of angular momentum by radiative damping (Press 1981;Schatzman 1993;Zahn et al 1997) and corotation resonances (Booker & Bretherton 1967;Alvan et al 2013). Their action induces important changes in the internal rotation profiles of stars during their evolution (Talon & Charbonnel 2008;Charbonnel et al 2013;).…”
Section: Introductionmentioning
confidence: 99%
“…Such amplitude equations are already used to investigate the driving of the atmospheric circulation by waves (Marks & Eckermann 1995). To conduct similar investigations in stars, it will be necessary to model energy deposition processes such as thermal dissipation and critical layers (Fritts et al 1998;Alvan et al 2013) and to take phase changes at caustics into account (Broutman et al 2004).…”
Section: Discussionmentioning
confidence: 99%